PEMBUKTIAN GRATIFIKASI SEKSUAL DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI - Marsella, Dian Dwi; Simangunsong, Frans (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Corruption crimes uses the theory of reverse proof or reversal of the burden of proof but in a balanced manner The type of evidence in this study is the type of proof of cases of gratification crimes. There are 2 problems studied in this study, namely the first, whether the proof of Gratification of sexual services in the procedural law of criminal acts in Indonesia The second, How to Expand the Meaning in Article 12b research using statutory approaches and concepts supported by prescriptive techniques. In eradicating the criminal act of gratification, this evidentiary system will be convicted if the defendant cannot prove the property he owns within the opportunity given by the judge in in court to be obliged to prove that the defendant did not commit a criminal act of gratification. The difficulty in the reverse application system in terms of legal substance is still weak because it is still limited to the recognition of the rights of the accused, not the obligation of the accused to carry out evidence